ANALYSIS OF TEACHING STRATEGIES OF SEKOLAH MURID MERDEKA (SMM) TEACHERS IN INCREASING THE EFFECTIVENESS OF TECHNOLOGY-BASED BLENDED LEARNING - Resya Sanita Wirakusumah; I Isrok'atun; Rana Gustian Nugraha (Jurnal Cakrawala Pendas, 2023)
In 2021 the Ministry of Education and Culture said that 60% of teachers still have limited mastery of ICT. As teachers who are constantly improving their teaching skills, developing their potential to realize the quality of learning by relying on technology is one way to increase competence in the application of ICT in the education sector. This research aims to describe the preparation of teaching strategies for teachers from schools that have implemented technology-based blended learning methods since 2019. This type of research is descriptive qualitative research using the case study method. Data collection methods used are interviews, observation, documentation, and questionnaires to support research. Interviews were conducted with the Head of the Elementary School Program, 2 offline teachers, 3 learning designers, and 1 online teacher, along with 17 teachers who filled out the questionnaire. From the results of research with questionnaires from 17 teachers, 82.6% strongly agreed and 17.6% agreed on the statement that the preparation of a teaching strategy consisting of a teaching-learning component in it is something that can increase the effectiveness of applied technology-based blended learning. Based on the results obtained, the teaching strategies that were developed before carrying out teaching and learning activities and in the process were considered to improve the quality and effectiveness of technology-based blended learning methods. Pada tahun 2021 Kementrian Pendidikan dan Budaya menyebutkan masih ada 60% guru yang penguasaan TIK-nya masih terbatas. Sebagaimana guru yang senantiasa meningkatkan kemampuan dalam mengajar, maka mengembangkan potensi diri demi mewujudkan kualitas suatu pembelajaran dengan mengandalkan teknologi salah satu cara untuk meningkatkan kompetensi dalam penerapan TIK dalam bidang pendidikan. Penelitian ini memiliki tujuan untuk mendeskripsikan penyusunan strategi mengajar guru dari sekolah yang menerapkan metode blended learning berbasis teknologi sejak tahun 2019. Jenis penelitian ini ialah penelitian deskriptif kualitatif dengan metode studi kasus. Metode pengumpulan data yang dilakukan adalah wawancara, observasi, dokumentasi dan angket untuk menunjang penelitian. Wawancara dilakukan bersama Kepala Program Sekolah Dasar, 2 orang guru luring, 3 orang learning designers, dan 1 orang guru daring, beserta 17 guru yang mengisi angket. Dari hasil penelitian dengan angket dari 17 guru, 82,6% sangat setuju dan 17,6% setuju atas pernyataan bahwa penyusunan strategi mengajar yang terdiri atas komponen belajar-mengajar didalamnya merupakan hal yang dapat meningkatkan efektivitas blended learning berbasis teknologi yang diterapkan. Bedasarkan hasil yang diperoleh bahwa strategi mengajar yang disusun sebelum melakukan kegiatan belajar-mengajar serta dalam prosesnya dinilai meningkatkan kualitas serta efektivitas dari metode blended learning berbasis teknologi.